Association of 18F‐Fluorodeoxyglucose–Positron Emission Tomography Activity With Angiographic Progression of Disease in Large Vessel Vasculitis. Issue 1 (8th December 2022) - Quinn, Kaitlin A.; Ahlman, Mark A.; Alessi, Hugh D.; LaValley, Michael P.; Neogi, Tuhina; Marko, Jamie; Novakovich, Elaine; Grayson, Peter C.
Abstract : Objective: To assess whether vascular activity seen on 18 F‐fluorodeoxyglucose–positron emission tomography (FDG‐PET) scan is associated with angiographic change in large vessel vasculitis (LVV). Methods: Patients with LVV were recruited into a prospective cohort. All patients underwent magnetic resonance angiography or computed tomography angiography and FDG‐PET imaging. Follow‐up imaging using the same imaging modalities was obtained ≥6 months later per a standardized imaging protocol. Arterial damage, defined as stenosis, occlusion, or aneurysm, and corresponding FDG uptake were evaluated in 17 arterial territories. On follow‐up, development of new lesions was recorded, and existing lesions were characterized as improved, worsened, or unchanged. Results: A total of 1, 091 arterial territories from 70 patients with LVV (38 patients with Takayasu arteritis, 32 patients with giant cell arteritis) were evaluated. Over a median 1.6 years of follow‐up, new lesions developed only in 8 arterial territories in 5 patients with Takayasu arteritis. Arterial lesions improved in 16 territories and worsened in 6 territories. Most arterial territories that did not have vascular activity on FDG‐PET scan at baseline had no angiographic change over the follow‐up period (787 [99%] of 793). Few territories with baseline FDG‐PET activity had angiographic change over time (24 [8%] of 298), but of the territories that developed angiographic change, 80% had FDG‐PET activity at baseline. Within the same patient, an arterial territory with baseline FDG‐PET activity had significantly increased risk for angiographic change compared to a paired arterial territory without FDG‐PET activity (odds ratio 19.49 [95% confidence interval 2.44–156.02]; P  < 0.01). Concomitant edema and wall thickening further increased risk for angiographic change. Conclusion: Development of angiographic change was infrequent in this cohort of patients with LVV. A lack of baseline FDG‐PET activity was strongly associated with stable angiographic disease. In cases of angiographic progression, change was preceded by the presence of FDG‐PET activity.